PERENCANAAN DAN PENGENDALIAN PRODUKSI DENGAN MENGGUNAKAN METODE MANUFACTURING RESOURCES PLANNING DI PT. SEMEN GRESIK Tbk - Iksan Iksan (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
PT. Cement Gresik represent big company which is moving in the field of construction material making (cement), where till now still execute the cement production for accomplishment of big enough target, although we know that in this time the economics of state still be drawn also raw material with maximal amount. Therefore to be able to productive in an optimal fashion need by the existence of a planning and controlling the raw material use. The application of manufacturing resources planning (MRP II) method is represent one of the method used for production planning and controlling which is exploited by as optimal as possible utilize to reach the target from production executor. With the MRP II analysis can calculate about the product amount produced, production time, also the raw material required so that knowable later whether the production plan need repair existence in the process or not. The result obtained from analysis that is with method MRP II i.e. the data patterns taken is Single ExponentialSmoothing with the smallest MAPE that is 19 %, while from the calculation of MRP II found on the result of MRP calculation about requirement of overall raw material experience increase equal to 3.920.653 ton/year and also at CRP calculation experience lack of production time capacities equal to 1528967,7 hour/period which is as the effect from the company policy in determination of the productions amount too high and also maximal machine capacities, so that needed by improvement in the production plan. Effort of repair mentioned by as an alternative that is by refunctioning machine which have time to be desisted and addition of the machine but cannot totally because capacities of maximal raw material existing also determination of production target the needed of seeing machine capacities.